Evaluating the efficacy of laterally positioned flap in the management of Miller's Class I and II gingival recession: A 6 months follow-up study - Rajendran, Poornima; Namburi, Rajesh (Eastern Journal of Medical Sciences, 2023)
Background: The goal of the study is to evaluate the clinical effectiveness of a laterally positioned flap (LPF) six months after it was used to correct Miller's Class I and II gingival recession abnormalities. Materials and methods: The LPF approach was used to treat 10 Miller's Class I or II gingival recession defects of height ≥3 mm (n = 10) on the labial surface of anterior teeth. At baseline, 3 months, and 6 months after surgery, clinical measures including probing pocket depth (PPD), clinical attachment level (CAL), width of attached gingiva (WAG), and height of gingival recession (HGR) were measured, and percentage of root coverage was calculated. Data were gathered, and repeated-measures ANOVA with the post hoc Bonferroni test was used for statistical analysis. Results: All clinical parameters such as PPD, CAL, WAG, and HGR showed improvement. All of the evaluated clinical measures showed statistically significant changes at post-operative 3 and 6 months compared to baseline values. With a p-value of